2005
DOI: 10.1191/1352458505ms1176oa
|View full text |Cite
|
Sign up to set email alerts
|

Motor determinants of gait in 100 ambulatory patients with multiple sclerosis

Abstract: A prospective analysis of gait and strength parameters was performed in 100 patients diagnosed with MS and pyramidal involvement admitted in a rehabilitation unit The patients were divided into two groups based on their ability to walk in daily life (nonassisted or cane-assisted gait) and into four clinical subgroups depending on associated involvements such as sensory loss or cerebellar ataxia. Twenty healthy subjects were studied as a control group. Gait parameters were evaluated with a Locometre and muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 24 publications
8
96
1
6
Order By: Relevance
“…Chung et al in 2008 observed that lower knee extensor power asymmetry was greater in individuals with MS than in controls [3]. Unilateral leg weakness has also been observed in individuals with MS [6][7]. In a 2011 study, Larson and White observed bilateral differences in hip bone density in ambulatory individuals with MS, which may illustrate consequences of altered bilateral function [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al in 2008 observed that lower knee extensor power asymmetry was greater in individuals with MS than in controls [3]. Unilateral leg weakness has also been observed in individuals with MS [6][7]. In a 2011 study, Larson and White observed bilateral differences in hip bone density in ambulatory individuals with MS, which may illustrate consequences of altered bilateral function [8].…”
Section: Introductionmentioning
confidence: 99%
“…The increased (hyper)extension during midstance resulting from first walking with the FES on may be a strategy used by the participants to counteract the action of the FES in assisting forward progression of the shank over the ankle. A possible reason for this may be to avoid increased eccentric loading of the knee extensors, indicated by the decreased knee extensor moment, which are known to be weak in people with MS [9,22] and a predictor of their walking performance [39]. The pattern of knee hyperextension was slightly greater when fatigued with the FES on which may have been done to further compensate for eccentric demands imposed on the knee extensors which are likely to have been weakened further after the fatiguing walk [21].…”
Section: Initial Orthotic Effect Of Fesmentioning
confidence: 99%
“…Perceptions of fatigue have also been associated with impaired central drive [20] contributing to a reduction in lower limb strength [21] which is a factor in gait deficits exhibited by people with MS [9,22]. The ankle dorsiflexor muscles are particularly susceptible to the effects of fatigue, with both central and peripheral factors, including impaired central drive, contributing to weakness of these muscles [23].…”
Section: Introductionmentioning
confidence: 99%
“…(12,13,14) Furthermore, several MRI studies tried to correlate MRI burden of the disease with walking impairment. (15,16) However, as the information provided by evoked potentials is more related to function unlike the information provided by MRI, which is more related to anatomy, evoked potentials may prove to be more useful in monitoring disease evolution in MS (17).…”
Section: Discussionmentioning
confidence: 99%